2018
DOI: 10.5045/br.2018.53.2.152
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of atypical patterns ofBCR-ABL1rearrangement and molecular-cytogenetic response to tyrosine kinase inhibitor therapy in newly diagnosed cases with chronic myeloid leukemia (CML)

Abstract: BackgroundTo analyze the frequency of atypical fluorescence in situ hybridization signal patterns and estimate the complete cytogenetic response (CCyR) and major molecular response (MMR) during 12 months of tyrosine kinase inhibitor therapy in patients with newly diagnosed chronic myeloid leukemia.MethodsThe study included bone marrow and peripheral blood samples from 122 patients with newly diagnosed chronic myeloid leukemia. Detection of the breakpoint cluster region—Abelson fusion gene (BCR-ABL1) was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Their findings suggest that CML patients in the accelerated phase or in blast crisis (AP/BC) with der(9) deletions show poor response to IM therapy. However, for CML patients in the chronic phase (CP), deletion of ABL1-BCR did not result in poor response to imatinib or lower rates of either complete cytogenetic or major molecular responses (Quintas-Cardama et al, 2011;Svabek et al, 2018). While it suggested that clonal copy number aberrations remain a hallmark of disease progression (Shao et al, 2015), the mechanism of the disease progression has not been fully illustrated.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings suggest that CML patients in the accelerated phase or in blast crisis (AP/BC) with der(9) deletions show poor response to IM therapy. However, for CML patients in the chronic phase (CP), deletion of ABL1-BCR did not result in poor response to imatinib or lower rates of either complete cytogenetic or major molecular responses (Quintas-Cardama et al, 2011;Svabek et al, 2018). While it suggested that clonal copy number aberrations remain a hallmark of disease progression (Shao et al, 2015), the mechanism of the disease progression has not been fully illustrated.…”
Section: Discussionmentioning
confidence: 99%
“…Derivative 9 deletions are also detectable by FISH analysis. The figure represents an ABL1 deletion of an interphase nucleus derived from Figure 2D from Švabek et al [107]. These are below the size resolution for detection using chromosome banding.…”
Section: Derivative Chromosome 9 Deletionsmentioning
confidence: 99%